Effect of initial pH in levan production by Zymomonas mobilis immobilized in sodium alginate - Queiroz Santos, Vidiany Aparecida [UNESP]; Del Bianchi, Vanildo Luiz [UNESP]; Garcia-Cruz, Crispin Humberto [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2014)
Zymomonas mobilis was immobilized using a cell suspension fixed to 8.6 x 10(7) CFU mL(-1) by spectrophotometry. This biomass was suspended in sodium alginate solution (3%) that was dropped with a hypodermic syringe into 0.2 M calcium chloride solution. Was test two initial pH of fermentation medium (4 and 5) and different sucrose concentrations 15, 20, 25, 30 and 35% at 30 degrees C, without stirring for 24, 48, 72 and 96 hours. The levan production to pH 4 was high in sucrose 25% for 24 (16.51 g L-1) and 48 (15.31 g L-1) hours. The best values obtained to pH 5 was in sucrose 35% during 48 (22.39 g L-1) and 96 (23.5 g L-1) hours, respectively. The maximum levan yield was 40.8% and 22.47% in sucrose 15% to pH 4 and 5, respectively. Substrate consumption to pH 4 was bigger in sucrose 15 (56.4%) and 20% (59.4%) and to pH 5 was in 25 (68.85%) and 35% (64.64%). In relation to immobilization efficiency, Zymomonas mobilis showed high adhesion and colonization in support, indicated by cell growth increased from 107 to 10(9) CFU mL(-1) during fermentation time.
Keywords: entrapment cell; batch fermentation; Biopolymer